Determinants of modern contraceptive use among married Somali women living in Kampala; a cross sectional survey - Maryan Abdulahi; Othman Kakaire; Fatuma Namusoke (BMC, 2020)
Abstract Background Low contraceptive uptake exposes women to unintended pregnancies and often the resultant obstetric complications. The immigrant communities especially from countries with low contraceptive use present a unique challenge. The main objective of the study was to describe modern contraceptive use and associated factors among married Somali women living in Kampala. Methods A community based cross sectional survey was conducted among Somali women living in Kampala from August to November 2016. Using consecutive sampling, 341 respondents were recruited after informed consent. Data was collected using interviewer administered questionnaires on contraceptives use and factors associated. Data was entered in Epidata 3.1 and analyzed using STATA 11.0. Logistic regression analysis was used to determine the factors associated with use of modern contraceptives. Results Majority of the participants were refugees 317/341(94%), with a mean age of 30.4 (±6.7) years and 136/341 (40%) had no formal education. More than 325/341 (95%) of respondents desired to have five or more children (Average 9 + 3) and 164/341 (45%) had five or more living children. Only 29% of women were using modern contraceptives, of which 51% used oral pills, 15% condoms and 15% injectables. Having tertiary education, one who had ever used modern contraceptives and desire for spacing of more than two years were independently associated with current of use modern contraceptives. Conclusions The Contraceptive prevalence rate among married Somali women in Kampala was (29%). A majority of the respondents were using short acting contraceptive methods. Attaining tertiary education, ever use of modern contraceptives, those whose source of contraceptive information was health worker and desire to space for more than two years were associated with current use of modern contraceptives. There is a need for improvement of girl child education, contraceptive awareness and male involvement to increase contraceptive uptake in this community. Research looking at attitude of this community towards use of long term contraception is recommended.